Sequential multiple retinal vein occlusions and transient ischemic attack in MTHFR polymorphism and protein S deficiency - Ahra Cho; Sara D. Ragi; Jin Kyun Oh; Jose Ronaldo Lima de Carvalho Jr; Joseph Ryu; Ber‐Yuh Yang; Stephen H. Tsang (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background The C677T variant of the MTHFR (5,10‐Methylenetetrahydrofolate reductase) gene is associated with increased susceptibility to homocystinuria (OMIM#236250), neural tube defects (OMIM#601634), schizophrenia (OMIM#181500), thromboembolism (OMIM#188050), and vascular diseases. Protein S deficiency is also associated with an increased risk of thromboembolism from reduced thrombin generation. In this report, we describe the case of a patient who presented with multiple retinal vein occlusions likely caused by an underlying combination of a homozygous MTHFR C677T variant and protein S deficiency. Methods We performed 8 years of continuous ophthalmic follow‐up of one patient diagnosed with central retinal vein occlusion. Peripheral blood was collected for metabolic evaluation and hypercoagulability assessment. Targeted gene sequencing was used for genetic diagnosis. Examination of the retinal vasculature was performed through dilated funduscopic examination, digital color fundus and ultrawide‐field color fundus photography, spectral domain optical coherence tomography, and fluorescein angiography. Results Sequential retinal vein occlusions and a transient ischemic attack were observed during the follow‐up period. Targeted gene sequencing by PCR identified the homozygous MTHFR C677T variant. The metabolic profile indicated low‐protein S activity, high levels of vitamin B6, and LDL cholesterol consistent with her hypercoagulable state. Prescription of low‐dose aspirin and atorvastatin for hypercholesterolemia resulted in no further neovascularization, leakage, or vein occlusion. Conclusion Retinal vein occlusions associated with the MTHFR C677T variant and protein S deficiency may signal impending systemic thromboembolic episodes and warrant aggressive preventative measures.